New views on physiological functions and regulation of butyrylcholinesterase and potential therapeutic interventions - Hajimohammadi, Samaneh; Lockridge, Oksana; Masson, Patrick (Frontiers in Molecular Biosciences, 2025)
Butyrylcholinesterase (BChE) is widely distributed in human tissues, although its physiological roles remain incompletely defined. It contributes modestly to cholinergic transmission and participates in lipid and ghrelin metabolism. BChE is pharmacologically and toxicologically significant due to its ability to hydrolyze various esters and neutralize toxic compounds such as carbamates and organophosphate (OP) pesticides and nerve agents. This review explores current insights into BChE functions and regulatory physiological mechanisms, with particular emphasis on its interaction with microRNAs (miRNAs) and defense against toxicants. BChE serves as a bioscavenger of OPs and reversible inhibitors, including several drugs and environmental chemicals. Moreover, its plasma activity is recognized as a valuable biomarker for disease prognosis, treatment monitoring, and the assessment of OP poisoning severity. Recent findings revealed a strong connection between specific miRNAs and BChE regulation, positioning these small non-coding RNAs as potential indicators of metabolic dysfunction and diverse pathological conditions. Additionally, miRNAs appear to modulate BChE expression in response to stress, inflammation, and immune responses. These discoveries highlight the potential of miRNA-based therapeutic approaches targeting BChE pathways in various clinical settings.